Assessment of Future Precipitation Changes in Mediterranean Climate Regions From CMIP6 Ensemble - Patricia Tarín‐Carrasco; Desislava Petrova; Laura Chica‐Castells; Jelena Lukovic; Xavier Rodó; Ivana Cvijanovic (International Journal of Climatology, 2025)
Previous studies have indicated a large model disagreement in the future projections of precipitation changes over Mediterranean climate (MedClim) regions worldwide. The majority of these highly populated regions have experienced major droughts in the recent decades, raising concerns about future precipitation changes and their impacts. Here, we examine precipitation projections in five MedClim regions from the CMIP6 ensemble, focusing on model consensus regarding the direction and magnitude of future precipitation changes. Our analysis spans the period 2050–2079 relative to 1970–1999, considering two climate change scenarios (SSP2‐4.5 and SSP5‐8.5) across the Mediterranean Basin (MED), California (CAL), the central coast of Chile (SAA), the Cape Province area of South Africa (SAF), and southwest Australia (AUS). The CMIP6 ensemble mean suggests that annual mean cumulative precipitation will decrease over all the regions except northern California, primarily due to a reduction in winter precipitation, and except over the Mediterranean Basin, where the most significant decrease occurs in autumn. Model agreement on the sign of future precipitation changes is high where the ensemble mean indicates a decrease, but lower where an increase or no changes are projected. Additionally, consecutive dry days (CDD) are expected to increase across all regions, whilst consecutive wet days (CWD) are expected to decrease. Maximum 1‐day precipitation is projected to increase uniformly across all regions. We conclude that despite substantial improvements to the new CMIP6 generation of models, the model spread in future precipitation projections in MedClim regions continues to be high. Impact studies need to account for these uncertainties and consider the whole intermodel range of projected precipitation changes.

Phenology and stem growth dynamics of Betula pendula Roth. in the Spanish Pyrenees - Xavier Castells-Montero; Emilia Gutiérrez-Merino (Trees, 2023)
Key message We established silver birch phenology in the Pyrenees. We highlight actual evapotranspiration as the main driver and the altitudinal effect within a north–south phenological pattern. Abstract Research into the phenology of trees is one of the most important issues in making reliable predictions of possible range shifts due to current climate change. Under the current climate change, warming and water stress can threaten tree performance by altering phenological events, specially at the edge of the southern especies distribution. We aimed at establishing bud burst, leaf and stem growth phenology of the Betula pendula in the Spanish Pyrenees, to determine the environmental cues triggering phenological events and to assess the effect of climate and soil water balance on annual growth cycle. The most important cues for bud burst are heat accumulation and long days that reduced the thermal time to bud burst. Leaf unfolding, the period of stem cambial activity, and the variation of the stem radial growth rates throughout the year are mainly regulated by the actual evapotranspiration. Leaf yellowing and abscission are advanced when hydric stress is pronounced shortening leaf longevity. The increase in spring temperatures brings forward the date of bud burst and the start of stem growth. However, the increase in the duration of hotter droughts causes an advance in the date of cessation of birch growth. From the southern Pyrenees to the boreal birch populations, there is a marked latitudinal gradient of phenological events, which are not linear except for the maximum stem growth rate. In the Pyrenees, the growing season is longer than in the boreal forests, but ring thickness is similar.

Potential of Transplanted Seagrass Meadows on Wave Attenuation in a Fetch-Limited Environment - Joan Pau Sierra; Vicente Gracia; Xavier Castell; Manuel García-León; César Mösso; Jue Lin-Ye (Journal of Marine Science and Engineering, 2023)
In this paper, the effectiveness of transplanted (either created or restored) seagrass meadows as a coastal protection measure is assessed through a five-step methodology. The analysis is focused on a stretch of the Catalan coast (NW Mediterranean) which is a fetch-limited environment. The results show that even considering conservative values for the meadow parameters (plant diameter, meadow density and canopy height), significant reductions of the annual average wave heights reaching the beach may be obtained, reducing flooding and erosion risks. Therefore, the investment in the conservation and restauration of seagrass meadows for protecting coastal areas from erosion and flooding is a measure that must be considered, due to the multiple benefits that they provide including ecosystem services. In addition, the proposed methodology may be a useful tool for coastal managers to help them in the design of seagrass meadows for coastal protection.

Life‐form diversity across temperate deciduous forests of Western Eurasia: A different story in the understory - Javier Loidi; Milan Chytrý; Borja Jiménez‐Alfaro; Nicola Alessi; Idoia Biurrun; Juan Antonio Campos; Andraž Čarni; Eduardo Fernández‐Pascual; Xavier Font Castell; Hamid Gholizadeh; Adrian Indreica; Ali Kavgacı; et al. (Journal of Biogeography, 2021)
Aim To analyse the biogeographic patterns of Temperate Deciduous Forests (TDFs) in Western Eurasia based on different life‐forms and forests layers and explore their relationships with the current climate, Last Glacial Maximum (LGM) climate and topography. Location Western Eurasia. Taxon Vascular plants. Methods We delimited nine regions encompassing the variability of TDFs in Western Eurasia and collected 1000 vegetation plots from each. We deconstructed the plant communities into three layers, tree, shrub and floor. We used (i) generalized linear mixed models (GLMM) to analyse the influence of current climate, historical climate and topography on species richness by accounting for regional effects and (ii) redundancy analysis (RDA) with variance partitioning to describe the variation in life forms along abiotic gradients. The three forest layers were analysed jointly and separately. Results The Balkans, Alps and Carpathians appeared to be the richest in plant species, whereas the British Isles and the Hyrcanian region were the poorest. Annual temperature range and annual mean temperature were the best predictors of species richness for the whole dataset and for the shrub layer. The tree layer richness was mainly explained by the annual temperature range and by elevation, whereas the forest floor richness was more related to the annual temperature range and the annual mean temperature differences between the LGM and current climate. The current climate was the main predictor of the composition of the whole community, the tree layer and the floor layer, while the shrub layer was also influenced by historical climate. Main conclusions Our overview of the diversity of temperate deciduous forests in Western Eurasia demonstrates different patterns and drivers across life‐forms and forest layers. While the diversity of trees is mainly linked to current climatic conditions, the shrub layer is also driven by postglacial‐glacial climatic stability, suggesting a different origin from forest trees.

Study of the strength of the evidence and the redundancy of the research on pharmacological treatment for Alzheimer’s disease: a cumulative meta-analysis and trial sequential analysis - Lídia Blanco-Silvente; Xavier Castells; Josep Garre-Olmo; Joan Vilalta-Franch; Marc Saez; Maria Antònia Barceló; Dolors Capellà (European Journal of Clinical Pharmacology, 2019)

Reduced seed predation after invasion supports enemy release in a broad biogeographical survey - Eva Castells; Maria Morante; José M. Blanco-Moreno; F. Xavier Sans; Roser Vilatersana; Anabel Blasco-Moreno (Oecologia, 2013)

Treatment discontinuation with methylphenidate in adults with attention deficit hyperactivity disorder: a meta-analysis of randomized clinical trials - Xavier Castells; Ruth Cunill; Dolors Capellà (European Journal of Clinical Pharmacology, 2013)

The Psychological Impact of a False-Positive Screening Mammogram in Barcelona - Rebecca Espasa; Cristiane Murta-Nascimento; Ramón Bayés; Maria Sala; Montserrat Casamitjana; Francesc Macià; Xavier Castells (Journal of Cancer Education, 2012)

Effects of compression stockings during exercise and recovery on blood lactate kinetics - Diana Rimaud; Laurent Messonnier; Josiane Castells; Xavier Devillard; Paul Calmels (European Journal of Applied Physiology, 2010)

Phenotypic characterization and risk factors for interval breast cancers in a population-based breast cancer screening program in Barcelona, Spain - Laia Domingo; Maria Sala; Sònia Servitja; Josep Maria Corominas; Francisco Ferrer; Juan Martínez; Francesc Macià; Maria Jesús Quintana; Joan Albanell; Xavier Castells (Cancer Causes & Control, 2010)

Association of MUTYH and MSH6 germline mutations in colorectal cancer patients - María Dolores Giráldez; Francesc Balaguer; Trinidad Caldés; Ana Sanchez-de-Abajo; Nuria Gómez-Fernández; Clara Ruiz-Ponte; Jenifer Muñoz; Pilar Garre; Victoria Gonzalo; Leticia Moreira; Teresa Ocaña; Joan Clofent; et al. (Familial Cancer, 2009)

Eyecup scope—optical recordings of light stimulus-evoked fluorescence signals in the retina - Thomas Euler; Susanne E. Hausselt; David J. Margolis; Tobias Breuninger; Xavier Castell; Peter B. Detwiler; Winfried Denk (Pflügers Archiv - European Journal of Physiology, 2009)

Capitalizing on Aggregate Data for Gaining Process Understanding––Effect of Raw Material, Environmental and Process Conditions on the Dissolution Rate of a Sustained Release Product - Karel Stryczek; Petr Horacek; Jiri Klema; Xavier Castells; Bob Stewart; Jean-Marie Geoffroy (Journal of Pharmaceutical Innovation, 2007)